Mangroves and Meaning-Making: A mutual relationship over time? Expert interview transcripts - Broocks, Anne-Katrin (PANGAEA, 2021)
EN: Transcriptions of semi-structured interviews held with stakeholders involved in mangrove management and/or mangrove use during field work in the mangrove areas of Southern Ecuador. Questions developed based on cultural domain analysis (Borgatti 1994, Bernard 2006:266ff., Schnegg and Lang 2008) and grand tour questions (Spradley 1979:86) within the theoretical framework of the Sociology of Knowledge. The lack of female voices is not only coincidently but symptomatic for the scientific and everyday-life (mangrove) discourse (cf. Merchant 1989 [1980], Haraway 1991, Harding 1991, Beard 2015, Cormier-Salem 2017).

ES: Transcripciones de entrevistas abiertas estandarizadas con stakeholders implicados en la gestión de manglares y/o el uso de manglares durante un trabajo de campo en los manglares de Ecuador del Sur. Cuestionario desarrollado basando en el cultural domain analysis (Borgatti 1994, Bernard 2006: 266ff., Schnegg and Lang 2008) y grand tour questions (Spradley 1979: 86) dentro del esquema teoretica de la Sociología del conocimiento. La falta de voces femininas no está coincidencialmente sino sintomático por el discurso científico y cotidiano de los manglares (cf. Merchant 1989 [1980], Haraway 1991, Beard 2015, Cormier-Salem 2017).
EN: This is a data collection of 20 expert interviews with different experts from universities, civil society, government and private sector dealing with mangroves. 5 of the experts were female, 16 were male. 18 interviews were conducted face-to-face, two interviews were conducted via Skype.

ES: Esto es una coleción de datos de 20 entrevistas con diferentes expertos de universidades, sociedad civil, gobierno y del sector privado relacionados a los manglares. 5 de los expertos son femeninos, 16 son masculinos. 18 de las entrevistas fueron realizados face-to-face, dos de las entrevistas fueron realizados via Skype.
Keywords: Data ID; File name; General data format; Data collection date; Gender, social sciences; Number of participants; Language; Occupation; Data collection methodology; Access type; Interview. Experteninterview; MAMM